Strategic Approaches in Coronary Intervention. - Ellis, Stephen G. (Wolters Kluwer Health, 2005)
Updated to include the newest devices and procedures, this practical reference is a clinically oriented guide to interventional cardiology. Chapters by the foremost experts present step-by-step approaches to specific clinical problems and offer guidelines for selecting the most appropriate device and technique. The authors' recommendations are backed by their extensive experience and by evidence-based clinical trials. This Third Edition describes the latest stents and stenting procedures-including local drug delivery with coated stents-and provides state-of-the-art information on local myocyte.